CBT for late‐life insomnia and the accuracy of sleep and wake perceptions: Results from a randomized‐controlled trial. (4th January 2019) - Dzierzewski, Joseph M.; Martin, Jennifer L.; Fung, Constance H.; Song, Yeonsu; Fiorentino, Lavinia; Jouldjian, Stella; Rodriguez, Juan Carlos; Mitchell, Michael; Josephson, Karen; Alessi, Cathy A.
Abstract: Subjective and objective estimates of sleep are often discordant among individuals with insomnia who typically under‐report sleep time and over‐report wake time at night. This study examined the impact and durability of cognitive‐behavioural therapy for insomnia on improving the accuracy of sleep and wake perceptions in older adults, and tested whether changes in sleep quality were related to changes in the accuracy of sleep/wake perceptions. One‐hundred and fifty‐nine older veterans (97% male, mean age 72.2 years) who met diagnostic criteria for insomnia disorder were randomized to: (1) cognitive‐behavioural therapy for insomnia ( n = 106); or (2) attention control ( n = 53). Assessments were conducted at baseline, post‐treatment, 6‐months and 12‐months follow‐up. Sleep measures included objective (via wrist actigraphy) and subjective (via self‐report diary) total sleep time and total wake time, along with Pittsburgh Sleep Quality Index score. Discrepancy was computed as the difference between objective and subjective estimates of wake and sleep. Minutes of discrepancy were compared between groups across time, as were the relationships between Pittsburgh Sleep Quality Index scores and subsequent changes in discrepancy. Compared with controls, participants randomized to cognitive‐behavioural therapy for insomnia became more accurate (i.e. minutes discrepancy was reduced) in their perceptions of sleep/wake at post‐treatment, 6‐months and 12‐months follow‐up ( p < .05). Improved Pittsburgh Sleep Quality Index scores at each study assessment preceded and predicted reduced discrepancy at the next study assessment ( p < .05). Cognitive‐behavioural therapy for insomnia reduces sleep/wake discrepancy among older adults with insomnia. The reductions may be driven by improvements in sleep quality. Improving sleep quality appears to be a viable path to improving sleep perception and may contribute to the underlying effectiveness of cognitive‐behavioural therapy for insomnia.